PENGARUH GAYA KEPEMIMPINAN, DAN MOTIVASI KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR KECAMATAN SEKUPANG BATAM - Sari, Dwi Utami; Mujib, Abdul; Rosita, Tita (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study was to analyze the effect of leadership style and principal's motivation on teacher performance in SD Sekupang District, Batam.This research is a correlation research.From the results of multiple regression analysis that the principal's motivational style variable has a greater value in influencing teacher performance.From the test results, it can be concluded that the leadership style and motivation of the principal simultaneously and significantly affect the performance of elementary school teachers in Sekupang District, Batam.From the results of the t test, it can be concluded that the leadership style variable has a significant influence on performance.Likewise, the principal's motivation has a significant effect on performance with a significant level of 0.05